Técnicas quirúrgicas simplificadas en cirugía mamaria - Fossati, Guillermo; Cerizola, María C (Cirugía del Uruguay, 1990)
The authors point out the advantages that simpler surgical techniques offer as compared to complex procedures. When similar results are to be expected, the most simple and less aggressive technique should always be chosen. The authors analyze techniques for treating breast gigantomastia and insist on the convenience of leaving the lowest number of scars as possible. As regards breas/ reconstruction, they present simple techniques that make satisfactory results possible without having to ressort to distan/ flaps. The resources employed are, according to each case, the subcutaneous expansor, the fat-free injection graft, and implant collocation.